Investigating the effect of source contamination on eXTP/SFA - Zhang, Juan; Li, Gang; Ge, Mingyu; Kirsch, Christian; Lorenz, Maximilian; Wilms, Jörn; Qi, Liqiang; Sheng, Lizhi; Yang, Yi Jung; Dauser, Thomas; Xu, Yupeng; Lu, Fangju; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
The Spectroscopy Focusing Array (SFA) onboard the enhanced X-ray Timing and Polarimetry (eXTP) observatory consists of 9 modules, each comprising a Wolter type I telescope with a field of view (FOV) around 16 arcminutes and a focal plane silicon drift detector (SDD) with 19 hexagonal pixels. Due to the large size of each individual SDD pixel (each pixel corresponds to an area of ∼ 3.6 arcminutes in diameter) and the limited pixel number, SFA can not obtain a real image of the observed region like many other X-ray imaging telescopes. Thus, contamination from nearby bright sources needs to be considered when we study the properties of the target source. We simulate such contaminations using the SIXTE simulator. In this paper we present the results by taking observations of the millisecond pulsar PSR J0437-4715 as an example, and discuss the cases for contamination on background or target source respectively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Contamination; EXTP/SFA; Nearby source